1987
DOI: 10.1007/bf00324551
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a combination of acetylcholinesterase reactivators, HI-6 and obidoxime, against tabun and soman poisoning of mice

Abstract: The bispyridinium oxime HI-6, 1-((((4-amino-carbonyl)pyridinio)methoxy) methyl)-2-(hydroxyimino)methyl)pyridinium dichloride monohydrate, combined with atropine is an effective treatment for soman (pinacolyl methylphosphonofluoridate) poisoning but is relatively ineffective against tabun (ethyl N-dimethyl phosphoroamidocyanidate) poisoning in mice. This contrasts with those results obtained using the bispyridinium oxime obidoxime[1,1'-(oxy bis(methylene)) bis(4-(hydroxyimino)methyl) pyridinium dibromide]. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…These results correspond to in vivo results from mice, rats and guinea-pigs published by several authors (4,18,25). It was found that the mixture of the oxime HI-6 and trimedoxime in the presence of atropine and diazepam ensures the higher degree of protection against poisoning by tabun, sarin and VX than the mixtures of HI-6 with pralidoxime or obidoxime (17).…”
Section: Discussionsupporting
confidence: 92%
“…These results correspond to in vivo results from mice, rats and guinea-pigs published by several authors (4,18,25). It was found that the mixture of the oxime HI-6 and trimedoxime in the presence of atropine and diazepam ensures the higher degree of protection against poisoning by tabun, sarin and VX than the mixtures of HI-6 with pralidoxime or obidoxime (17).…”
Section: Discussionsupporting
confidence: 92%
“…In the cases of toxogonin and TMB-4, two of the most efficient oximes in the treatment of tabun poisoning (Clement 1983) there are two oxime groups in the 4 position; one in each of the pyridinium rings. However, it must be emphasized, especially in the case of HI-6, that the reactivation of tabun inhibited acetylcholinesterase does not seem to be a prerequisite for the therapeutic benefit of the oxime to be realized (Clement et al 1987). HI-6 was ineffective against tabun poisoning in mice (Clement 1983) and did not reactivate tabun inhibited acetylcholinesterase (Clement et al 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Pyridinium compounds reversibly bind to the AChE active site and interfere with the binding of phosphorylating agents 11 . In the case of imminent threat of tabun exposure, pretreament should have an important role, because tabuninduced deleterious effects are extraordinarily difficult to counteract with currently used oximes 8,9,20,36 . In order to improve the efficacy of standard therapy, we determined the protective index of various combinations of atropine, oximes, and pyridostigmine given to mice before tabun poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Although the oxime TMB-4 reactivates tabun-inhibited AChE showing beneficial effects in tabun-poisoned animals [6][7][8] , it is the most toxic of the four most investigated oximes: 2-PAM (pralidoxime chloride), HI-6, obidoxime, and TMB-4 9 . Therefore, there is still a need to develop not only the most effective, but also the least toxic, organophosphate antidote.…”
Section: Introductionmentioning
confidence: 99%